Production of low protein and gluten-free cookies for phenylketonuria (PKU) and/or celiac patients - Parlak, Özen; Dündar, Ayşe Neslihan (Czech Academy of Agricultural Sciences, 2021)
The aim of this study was to analyse the production of gluten-free, low protein cookies, which can easily be consumed by celiac and phenylketonuria (PKU) patients. The formula was adopted to prepare the control cookies (without dried fruits) from maise starch, stabilisers, salt, sodium bicarbonate, protein-reduced milk powder, and sunflower oil. Different cookies were made by adding raisins (R), dried black currants (Cu), dried dates (D), dried apples and cinnamon (A) separately. In cookies, two different stabilisers were calculated according to starch weight [pectin (P): 0.15%, glycerol monostearate (GMS, G): 0.4%]. The effects of stabilisers and dried fruits on the physicochemical and sensory properties of cookies were investigated. The protein content was significantly higher (P < 0.05) in the cookies including R with pectin (PR), Cu with pectin (PCu), and A with pectin (PA). The amount of phenylalanine (Phe) was significantly higher (P < 0.05) in PR. The values of dietary fibre were the highest in the A cookies, while the lowest values appeared in the control (C). In the sensory evaluation (appearance, tasting properties, and affordability), it was found that PD (pectin with dries dates) was chosen as the best cookie (P < 0.05).
Keywords: Celiac disease; Cookie; Dried fruits; Stabiliser